Effect of isotropic stress on dislocation bias factor in bcc iron: an atomistic study. Issue 1 (2nd January 2018) - Bakaev, A.; Terentyev, D.; Chang, Z.; Posselt, M.; Olsson, P.; Zhurkin, E. E.
Abstract: The effect of externally applied stress on the dislocation bias factor (BF) in bcc iron has been studied using a combination of atomistic static calculations and finite element integration. Three kinds of dislocations were considered, namely, a 0 /2〈1 1 1〉{1 1 0} screw, a 0 /2〈1 1 1〉{1 1 0} edge and a 0 〈1 0 0〉{0 0 1} edge dislocations. The computations reveal that the isotropic crystal expansion leads to an increasing or constant dislocation bias, depending on the Burgers vector and type of dislocation. On the other hand, compressive stress reduces the dislocation bias for all the dislocations studied. Variation of the dislocation BF depending on dislocation type and Burgers vector is discussed by analysing the modification of the interaction energy landscape and the capture efficiency values for the vacancy and self-interstitial atom.